2014
DOI: 10.1016/j.cgh.2014.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Applications and Advancements in the Use of High-resolution Microendoscopy for Detection of Gastrointestinal Neoplasia

Abstract: The high-resolution microendoscope (HRME) is a novel imaging modality that allows real-time epithelial imaging at subcellular resolution. Used in concert with any standard endoscope, this portable, low cost, ‘optical biopsy’ technology has the ability to provide images of cellular morphology during a procedure. This technology has been the subject of a number of studies investigating its use in screening and surveillance of a range of gastrointestinal neoplasia, including esophageal adenocarcinoma(EAC), esopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…High-resolution microendoscopy (HRME) allows the user to conduct high-quality, real-time imaging at the cellular level in vivo [27] , [28] . HRME is therefore becoming an adjunct to established screening modalities to enhance the detection of precancerous and cancerous lesions at multiple sites, including the esophagus, colon, and cervix, as well as the oral cavity and gastrointestinal tract [29] [32] . Particularly relevant for low-resource settings where access to traditional pathology services is limited, HRME can become a valuable tool to enhance screen-and-treat programs, especially as the development of smartphone-based image analysis programs bolsters the diagnostic capacity of the imaging modality [25] , [33] .…”
Section: Imaging Technologies For the Detection And Diagnosis Of Cancmentioning
confidence: 99%
“…High-resolution microendoscopy (HRME) allows the user to conduct high-quality, real-time imaging at the cellular level in vivo [27] , [28] . HRME is therefore becoming an adjunct to established screening modalities to enhance the detection of precancerous and cancerous lesions at multiple sites, including the esophagus, colon, and cervix, as well as the oral cavity and gastrointestinal tract [29] [32] . Particularly relevant for low-resource settings where access to traditional pathology services is limited, HRME can become a valuable tool to enhance screen-and-treat programs, especially as the development of smartphone-based image analysis programs bolsters the diagnostic capacity of the imaging modality [25] , [33] .…”
Section: Imaging Technologies For the Detection And Diagnosis Of Cancmentioning
confidence: 99%
“…The probe is small and portable and can be reused about 60 to 75 times, and current prototypes have been built for less than $3500. 61 An initial study showed the feasibility of HRME to assess ex vivo endoscopic mucosal resection (EMR) specimens in patients with a prior diagnosis of BE with HGD or adenocarcinoma. 62 One study compared 20 gastroenterologists with no prior microendoscopic experience to 3 endoscopists who had performed greater than 50 HRME cases in assessing HRME images.…”
Section: Emerging Technologiesmentioning
confidence: 99%
“…PRO is also known to have a mutagenic effect on DNA by intercalating between nucleic acid base pairs; this makes PRO a special type of mutagenic compound because it causes base pair-deletions or base pair-insertions rather than substitutions. In the presence of light, PRO can also induce double-stranded breaks in DNA [7,8].…”
Section: Introductionmentioning
confidence: 99%